Civil Religion-Based Society; The Contribution of Shalawat Pettengan to the Character Building of Negorejo Community, Probolinggo, East Java - Herwati (Tribakti: Jurnal Pemikiran Keislaman, 2023)
The rise of theft, robbery, gambling and drug users by the youth of Negorejo Village, Lumbang District, Probolinggo Regency causes mental loss, addiction, and prolonged depression that can affect their peers and minors. The presence of Hadratus Shaykh Habib Ali Bin Muhammad al-Habsyi in 2017 brought solutions and significant changes in overcoming one of these problems by establishing the Pettengan Shalawat Council. The Pettengan Shalawat Assembly is a prayer assembly held at night to instill character values. Since the implementation of Shalawat Pettengan, youths are more civilized and have character; this is evidenced by the low level of drug users by young people, who are starting to realize the true meaning of life and the purpose of life. The implementation of the Pettengan Shalawat aims to grow awareness in shaping the character of youth and society so that they can communicate and establish good relationships with God (hablun min Allah) and others (hablun minannas). In this case, the existence of the Pettengan prayer meeting can direct, guide, and make people moral, dignified, and have a character so that they are helpful to the nation and religion.